Buru Babi: Politik Identitas Laki-laki Minangkabau - Zainal Arifin (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
Minangkabau is widely known for its matrilineal system. One of the matrilineal values is the man (sumando) that positioned as marginal. Sumando is a stranger in his wife's family, as shown in the traditional proverb saying like ashes on the stump (seperti abu di atas tunggul). This position is not profitable, so they have to negotiate with the woman as a